An Algorithm to Balance Supply and Use Tables - Stanger, Michael (Technical Notes and Manuals; Technical Notes and Manuals ;, 2018)
A Supply and Use Table (SUT) serve to increase the quality of GDP and related aggregates by providing a framework to detect and resolve inconsistencies in data sources. SUTs are also a powerful analytical tool that permit users to access information on detailed production functions, consumption, export, and import baskets, or to derive input-output tables. SUT compilation is data intensive and requires a balancing process. The balancing procedure is labor intensive and generally requires several long and sometimes tedious iterations, which has an adverse effect on timeliness. This note describes a basic algorithm developed by the IMF to balance supply and use tables automatically, allowing a much faster SUT balancing process. For training purposes, this algorithm has been implemented as an Excel tool SUTB, making it operational almost globally. The optimization process is illustrated with an example.